Heavy Metals (Pb and Cu) Pollutant Concentrations in the Water and Sediments of the Southern Coast of Karimun Besar Island Riau Archipelago - Hafandy '; Budijono '; M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
In the Karimun Besar Island, there are tin industries and it may produce heavy metal pollutant that contaminate the surrounding waters. To understand the lead (Pb) and copper (Cu) concentration in the coastal waters of the island, a research was conducted in December-January 2016. There were 3 stations, around the fishermen village (S1); in the harbor (S2) and in the recreation area (S3). Water and sediment were sampled 3 times, once/ 2 days. The samples were then analyzed using an AAS. Results shown that the highest Pb concentrations in the seawater and fresh water are obtained in the S2 (0,1865 mg/L and 0.0642 mg/L respectively), while the highest Pb in the sediment was in the S1 (0,1942 g/g). The highest Cu concentration in the seawater was in the S1 (0,0388 mg/L), while the highest Cu concentration in the freshwater and sediment was in the S3 (0,0317 mg/L and 0,1296 g/g respectively). In general, the concentration of Pb and Cu in the Southern Coast of the Karimun Besar Island is normal, its values are below the ERL and ERM standard. Based on the Igeo standard, the sediments can be categorized as non-polluted.Keyword : Heavy Metal, Seawater, Sediment, Karimun, Lead, Copper